Assessment of species richness in Lake Dal, Kashmir, based on classical approach, physiological approach and rDNA ITS sequences from isolates. (March 2017) - Bandh, Suhaib A.; Kamili, Azra N.; Ganai, Bashir A.; Lone, Bashir A.
Abstract: As a first description to document the species richness in Dal Lake, a freshwater lake ecosystem in Kashmir valley, an extensive network of sixteen sampling stations with distinguishing features was sampled seasonally for two years. The identification process yielded fifty-one species probably first and new records for this area to date. The taxonomic groups observed were those with species from Ascomycetes (inclusive of yeasts), Basidiomycetes, Blastocladiomycetes, Zygomycetes, and Peronosporomycetes. Each phylum was represented by a single Order, with the exception of the Peronosporomycetes, which was represented by two Orders- Saprolegniales and Pythiales. In the filamentous fungal group, family Trichocomaceae was dominant followed by Saccharomycetaceae, Mucoraceae, Nectriaceae, Tremellaceae and Hypocreaceae. However, in the group of zoosporic & fungal like eukaryotes, family Saprolegniaceae was most dominant followed by Blastocladiaceae and Pythiaceae. A dramatic decrease in fungal load was observed in different seasons with highest colonial load in the summer season and lowest in the winter season. The observed distribution was statistically significant for both the filamentous fungal species (p < 0.01) as well as zoosporic fungi & fungal like eukaryotes (p < 0.05). In order to assess biodiversity patterns of fungi more accurately, it is necessary to repeat such investigations in other areas and to improve the tools for taxonomic identification of these highly diverse but mostly microscopic organisms. Highlights: This study resulted in the isolation of a variety of both fungal and fungal like eukaryotes from the lake water. Amplification of the ITS region of the rDNA proved to be an effective and efficient tool in the exact identification work. Seasonal influence on the occurrence of fungal and fungal like organisms in the lake water is quite promising. This is the first such detailed study vis-à-vis the species richness of any lake in the state of Jammu & Kashmir.